Efeito citotóxico e antitumoral da Bothropstoxina-I e da Crotamina - Costa, Luiz Carlos Gebrim de Paula (2005)
BthTX-I and Crotamine are non enzymatic myotoxins isolated from Bothrops jararacussu venom and Crotalus durissus terrificus respectively. The aims of this work were to evaluate the action of BthTX-I (native or modified) and crotamine (in vitro) on cells lines and on the bacterial proliferation; and the native and modified BthTX-I on the growth of the tumor induced by the Sarcoma 180 (S180) in mice. The in vitro assays showed that native and modified BthTX-I and crotamine incubated separately in different concentrations with different cells lines, reduced the cellular viability in a dose dependent manner. BthTX-I (1µg/µL) produces 100% cellular death on Jurkat, 90% in macrophages, S180 and B16F10, 45% in Sk-BR-3; while BthTX-I BPB (1µg/µL) showed 20-40% of cytotoxicity on all of cellular lines. BthTX -I modified in the Tyr and Trp residues, showed 50-60% of cytotoxicity for S180 and 20-40% for macrophages. Crotamine (1µg/µL) showed of 75% on S180 and 20% on macrophages. The bactericidal activity of BthTX-I (0, 8 µg /µL) against E. coli and S. aureus was of approximately 100%, while the chemical modification reduced this activity Mice (n=5) inoculated with S180 in the groin (i.m.) developed a tumor developed a solid tumor that became evident after 5 days, presenting histological alterations. BthTX-I and BthTX-I BPB (50µg/µL, i.m.) injection administered in mice on the 5th day after the inoculation of S180 cell in the groin (i. m.) reduced the tumor volume in 30% in the 14th day and 80% in the 60th day, besides reducing the histological alterations. These results demonstrate that BthTX-I and crotamine possess hight cytotoxic activity on the cellular lines tested in vitro and the cytotoxicity of BthTX-I after the modification by BPB was lower suggesting that the His residue has an important role in the cytotoxicity; the inhibition of the growth of the solid tumor in mice treated with BthTX- I or BthTX-I BPB were similar, suggesting that the mechanism antitumoral of the toxin can be independent of the cytotoxicity activity.